Exploring crossmodal correspondences for future research in human movement augmentation - Pinardi, Mattia; Di Stefano, Nicola; Di Pino, Giovanni; Spence, Charles (Frontiers in Psychology, 2023)
“Crossmodal correspondences” are the consistent mappings between perceptual dimensions or stimuli from different sensory domains, which have been widely observed in the general population and investigated by experimental psychologists in recent years. At the same time, the emerging field of human movement augmentation (i.e., the enhancement of an individual’s motor abilities by means of artificial devices) has been struggling with the question of how to relay supplementary information concerning the state of the artificial device and its interaction with the environment to the user, which may help the latter to control the device more effectively. To date, this challenge has not been explicitly addressed by capitalizing on our emerging knowledge concerning crossmodal correspondences, despite these being tightly related to multisensory integration. In this perspective paper, we introduce some of the latest research findings on the crossmodal correspondences and their potential role in human augmentation. We then consider three ways in which the former might impact the latter, and the feasibility of this process. First, crossmodal correspondences, given the documented effect on attentional processing, might facilitate the integration of device status information (e.g., concerning position) coming from different sensory modalities (e.g., haptic and visual), thus increasing their usefulness for motor control and embodiment. Second, by capitalizing on their widespread and seemingly spontaneous nature, crossmodal correspondences might be exploited to reduce the cognitive burden caused by additional sensory inputs and the time required for the human brain to adapt the representation of the body to the presence of the artificial device. Third, to accomplish the first two points, the benefits of crossmodal correspondences should be maintained even after sensory substitution, a strategy commonly used when implementing supplementary feedback.